Present and Future of Industrial Robotisation - Buri, Zsolt (International Journal of Engineering and Management Sciences, 2024)
The following paper analyzing the installation of industrial robotisation in sectors and regions, in addition carry out forcastings on historical data. In recent years, automation and the use of industrial robotics have increased exponentially in the manufacturing sector. Given that companies prioritize enhanced production efficiency, quality assurance, and safety, it is evident that substantial investment and implementation of automation continue to occur in manufacturing facilities worldwide. The number of industrial robots globally has been growing steadily since 2010. However, the rate of growth has slowed from 2020 onwards. The impact of the Covid-19 epidemic was still felt in 2020, but the deployment of industrial robots increased significantly in 2021. Global industrial robot deployment is projected to continue to grow in the coming years, although the rate of increase may vary between regions and countries. The analysis showed a number of differences between regions in the number and growth rate of industrial robot deployments. Asia and Australia are the largest markets for robots and the number of robots deployed is expected to continue to grow in the future. Europe is the second largest market and, although growing at a slower rate, industrial robot deployment is also increasing steadily. In the Americas, growth is slower than in other regions, but still increasing. Global growth trends suggest that there will be further growth in the coming years and that the deployment of industrial robots will become more widespread in different parts of the world.